2011
DOI: 10.1186/1758-2652-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and inflammation serum biomarkers are associated with 12‐week mortality among malnourished adults initiating antiretroviral therapy in Zambia

Abstract: BackgroundA low body mass index (BMI) at antiretroviral therapy (ART) initiation is a strong predictor of mortality among HIV-infected adults in resource-constrained settings. The relationship between nutrition and inflammation-related serum biomarkers and early treatment outcomes (e.g., less than 90 days) in this population is not well described.MethodsAn observational cohort of 142 HIV-infected adults in Lusaka, Zambia, with BMI under 16 kg/m2 or CD4+ lymphocyte counts of less than 50 cells/mm3, or both, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
1
25
0
Order By: Relevance
“…Higher levels of ferritin before ATT were not observed among smokers, alcoholics and HIV infected subjects as described by others [11,23]. Higher CRP and ferritin levels before ATT were however associated with older age, and low BMI as described by Isanaka et al [19].…”
Section: Discussionmentioning
confidence: 62%
“…Higher levels of ferritin before ATT were not observed among smokers, alcoholics and HIV infected subjects as described by others [11,23]. Higher CRP and ferritin levels before ATT were however associated with older age, and low BMI as described by Isanaka et al [19].…”
Section: Discussionmentioning
confidence: 62%
“…31 Malnourishment during the initial 12 weeks of antiretroviral therapy has also been shown to increase systemic inflammation and mortality. 32 The effectiveness of inflammatory markers in indicating mortality risk has been shown to be affected by malnourishment. In dialysis patients, Hung et al 33 reported that C-reactive protein (CRP), typically associated with higher mortality, was not linked with mortality in patients with good nutritional status, but a strong link between CRP and mortality was observe in malnourished patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the first 90-180 days of ART, the mortality rate among undernourished HIV-infected adults is over 25% in some settings, which is 4 to 6-fold higher than HIV-infected adults with normal BMI and is independent of CD4 T-cell suppression [1-4]. While the etiology of the high early mortality is likely multifactorial, persistent, heightened systemic inflammation is a major risk factor for death in undernourished, HIV-infected adults starting ART in the region [5, 6]. …”
Section: Introductionmentioning
confidence: 99%